Calculation of Lorentz force in planar EMAT for thickness measurement of steel plate. Issue 4 (3rd July 2017) - Tu, Jun; Chen, Tao; Xiong, Zhi; Song, Xiaochun; Huang, Songling
Abstract : Purpose: The aim of this paper is to better understand the generation and transmission mechanism of the electromagnetic acoustic transducer (EMAT). Design/methodology/approach: A semi-analytical method was used to calculate the Lorentz force. Both the hypothetical magnetic field mirror method and the diffusion equation were adopted to solve the eddy current distribution by variables separation method in time domain. A three-dimension magnetostatic finite element model was used to calculate the static magnetic field and the relative permeability. And an experimental platform with a piezoelectric probe to generate and an EMAT to receive, the ultrasonic wave was set up to verify the distribution of the Lorentz force. Findings: The Lorentz force at different time and in different positions of the steel plate can be easily calculated. The experimental results show a good agreement with the analytical results. Originality/value: The accurate prediction of the Lorentz force provides an insight into the physical phenomenon of EMAT and a powerful tool to design optimum EMAT.